Narrative Network Analysis on Social Media Concerning the XYZ Ministry in Indonesia: Constructive Criticism vs. 'Pseudo-Haters' - Said, Martriana Ponimin; Rospitasari, Marina (Jogjakarta Communication Conference (JCC), 2025)
This article analyses the network of narratives circulating on social media regarding the XYZ Ministry in Indonesia, focusing on distinguishing between constructive criticism and the activities of "pseudo-haters." Criticism of government institutions on social media often intertwines with destructive and constructive negative narratives. Through narrative network analysis, this research aims to identify interaction patterns and information dissemination that indicate the presence of groups spreading unfounded negative narratives classified as "pseudo-haters." Social media has emerged as the primary platform for the public to express aspirations and criticisms; however, it is also susceptible to spreading harmful narratives that tarnish the institution's image. This article employs a narrative network analysis approach to identify key actors, narrative themes, and information dissemination patterns related to the XYZ Ministry. The research results are anticipated to map the current narrative landscape and uncover the presence of "pseudo-haters" groups that may contribute to the spread of factually unfounded negative narratives. These results are expected to provide a deeper understanding of the dynamics of criticism and the dissemination of negative narratives on social media, along with their implications for Ministry XYZ's reputation and public communication.